2000
DOI: 10.1097/00000658-200008000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/Permeability-Increasing Protein Preserves Leukocyte Functions After Major Liver Resection

Abstract: ObjectiveTo analyze postoperative leukocyte functions in patients undergoing hemihepatectomy, and to assess the effect of treatment with the endotoxin-neutralizing agent bactericidal/permeability-increasing protein (rBPI 21 ). Summary Background DataExtensive liver resection is associated with a high incidence of infectious complications. Because elimination of pathogenic microorganisms occurs mainly by leukocytes, this increased rate of infections is most likely due to an impaired function of these cells. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Yet it might be argued that the presence of elevated levels of LBP remains an indirect clue as to the role of endotoxin, as some other factors might stimulate LBP induction. However, this approach is also supported by the work of other authors (21–23) who have used LBP as a suitable indicator of endotoxaemia in different settings.…”
Section: Discussionmentioning
confidence: 73%
“…Yet it might be argued that the presence of elevated levels of LBP remains an indirect clue as to the role of endotoxin, as some other factors might stimulate LBP induction. However, this approach is also supported by the work of other authors (21–23) who have used LBP as a suitable indicator of endotoxaemia in different settings.…”
Section: Discussionmentioning
confidence: 73%
“…The mechanisms that initiate these responses are not known, but it has been suggested that the decreased ability of the resected liver to clear endotoxins released by the gut results in Kupffer cell activation (43). This activation in response to decreased innate immunity function parallels the activation of FXR by increased bile acid flux.…”
Section: Research Articlesmentioning
confidence: 99%
“…Recombinant BPI (rBPI 21 ) is a 21-kDa amino-terminal protein derived from the 55-kDa human BPI 55 . RBPI 21 has the same bactericidal properties as the endogenous BPI [25,26]. The main object of this study was to determine the effects of liver surgery on the angiogenic profile in the circulation.…”
Section: Introductionmentioning
confidence: 99%